Is Acceptance and Commitment Therapy Effective in Improving Emotion Regulation in Single Mothers? - Tiffany, Aulia; Nur, Badrut Tamam; Ratna, Dwi; Putri, Novika; Putri, Pingkan; Anto, Abdul Haris Fitri (International Conference on Sustainable Health Promotion, 2023)
Being a single parent is not an easy challenge. The ability to manage emotions in single mothers who play the role of caring for children, carrying out domestic household affairs, and working to meet family needs must be truly organised so that all agendas run as planned. However, the reality shows that many single mothers physically and emotionally struggle. This research aims to determine the effectiveness of the ACT (acceptance and commitment therapy) method in improving emotional regulation in single mothers. This research applied a one-group pretest-posttest experimental design involving ten single mothers who were selected randomly. Pretest-posttest data collected using the Difficulties in Emotion Regulation Scale (DERS) by Gratz and Roemer (2004) showed a decrease in the mean. This means that there is an increase in the ability to regulate emotions. In addition, the results of the paired t-test showed that the decrease in score was significant (p) 0.00 (<0.05). With these results, ACT intervention can significantly improve emotional regulation in single mothers. The results of this research will be discussed further.